Penggunaan Scrapbook dan Flipchart Sebagai Media Peningkatan Pengetahuan Kesehatan Gigi dan Mulut - Priyambodo, Ardian; Liasari, Ira; Supriatna, Agus; Jumriani; Mukmin, Nurhidayah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Dental and oral health is a critical aspect of overall well-being, as untreated dental and gum issues can lead to pain, impaired chewing ability, and potentially disrupt overall health. This is particularly important for school-aged children, who are especially vulnerable to dental health problems. Notably, the prevalence of tooth decay, cavities, and oral diseases is highest among children aged 5-9 years, with an incidence rate of approximately 54.0%. This research aims to compare the effectiveness of scrapbooks and flipcharts as educational media for enhancing dental and oral health knowledge among students at SDN 133 Pewa, Pasui Village, Buntu Batu District, Enrekang.This study employs a quantitative experimental design with a quasi-experimental approach, utilizing a two-group pre-test and post-test format. The sampling technique used was quota sampling, encompassing a total of 30 students—15 assigned to the scrapbook group and 15 to the flipchart group. Data analysis was conducted using the Wilcoxon test and Mann-Whitney test to evaluate the outcomes.The findings indicate a significant improvement in dental and oral health knowledge post-intervention in both groups. The Mann-Whitney test result revealed a p-value of 0.004, indicating a significant difference in effectiveness between the scrapbook and flipchart educational interventions. Both scrapbook and flipchart media were effective in increasing students' knowledge of dental and oral health, with a notable difference in their impact. The study underscores the importance of selecting appropriate educational tools to enhance health knowledge among school-aged children.